Journal publishing with Acrobat: the CAJUN project - Smith, Philip N.; Brailsford, David F.; Evans, David R.; Harrison, Leon; Probets, Steve G.; Sutton, Peter E. (John Wiley & Sons Ltd, 1993)
The publication of material in electronic form should ideally preserve, in a unified document representation, all of the richness of the printed document while maintaining enough of its underlying structure to enable searching and other forms of semantic processing. Until recently it has been hard to find a document representation which combined these attributes and which also stood some chance of becoming a de facto multi-platform standard.